EKSPLORASI PENYAJIAN LAPORAN KEUANGAN DAN AKSESIBILITAS INFORMASI PENGGUNAAN LAPORAN KEUANGAN DAERAH PROVINSI BENGKULU - Oktasari, Dwince; saiful, saiful; Aprila, Nila (JURNAL FAIRNESS, 2020)
This study aims to review, discuss and prove the presentation of financial statements and the accessibility of financial information to the use of financial statement information. This research was conducted in the Provincial DPRD, Inspectorate and BPK with a total of 47 respondents. Data were collected using a research questionnaire and processed using multiple linear regression. The results showed that the financial statements and the accessibility of positive and significant information on the use of Bengkulu Province regional financial statement information. Hoping the better financial statement presentation and information accessibility will increase the use of financial statement information.